Gastronomic Aesthetics of a French Catholic Missionary during the Japanese Occupation of Malaya - Pillai, Shanthini (SARE: Southeast Asian Review of English, 2023)
Much has been written about British accounts of colonial Malaya from the perspective of travellers, explorers, novelists, historians and many more. Much also exists on the Malaysian responses to life under the Japanese Occupation. Yet there is a lacuna on scholarship on other European communities that existed alongside the British in Malaya. This paper traces the French oeuvre of the Japanese Occupation of Malaya, especially within the context of food and religiosity. Focusing on a diary written by a French Catholic missionary in Malaya during the Japanese Occupation, it interrogates the aspect of Catholic gastronomic aesthetics through the concepts of the imaginary of incorporation as well as biblical metaphors of commensality. In so doing, the paper presents a different and novel angle to existing conversations on European networks of knowledge production on colonial Malaya, especially within the context of food and colonialism, revealing that not all frameworks of the operations of European colonialism are the same. It also significantly intervenes into and alters the vestiges of a colonial palate that has heretofore remained predominantly British through the foregrounding of a French Catholic cultural perspective that perceptibly adds its own distinct flavour. Keywords: Japanese Occupation; British Malaya; French missionaries; Food colonialism; Catholicism; Gastronomic aesthetics